Death on the caldera - Paxman, Emily (Titan Books, 2025)
"The Linde siblings--Kellen, Davina, and Morel--are anxious to return to the kingdom of Halgyr before their father dies, leaving Kellen to assume the throne as king ... but disaster strikes when the train engine explodes, stranding the siblings atop a caldera bubbling with volcanic magic. The crash triggers Davina's latent witch powers ... While a witch would be the prime suspect for the catastrophe, the only ones who knew Davina might become one are her brothers--who never warned her ... While the remaining passengers try to determine who sabotaged the engine and catch the killer, the fractured siblings attempt to stay one step ahead, concealing not only Davina's powers but their own secrets"--